2016
DOI: 10.22495/cocv13i2c1p1
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and intellectual capital disclosure. An empirical analysis of the Italian listed companies

Abstract: Intellectual capital (IC) as well as disclosure of information on IC has in recent years gained importance. IC is the key issue in strengthening a firm’s competitive position and in achieving its objectives. The purpose of this study is to investigate some determinants of the disclosure of IC in annual reports. In particular the aim of this research is to analyse the internal mechanisms of corporate governance (board composition, role duality, ownership structure, auditor type and size of audit committee), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 134 publications
5
15
1
3
Order By: Relevance
“…The results of most of these studies showed a better corporate governance increases the awareness of companies in expressing intellectual capital and this consequently means the disclosure becomes wider (Abeysekera, 2010;Ahmed Haji & Mubaraq, 2015;Akben-Selcuk & Sener, 2019;Taliyang & Jusop, 2011) but a contrasting finding was reported by Yan (2017). Meanwhile, mixed results were recorded by Appuhami and Bhuyan (2015); Baldini and Liberatore (2016) and this was suggested to be due to the variables used in measuring corporate governance sincere there were no universally agreed measures (Akben-Selcuk & Sener, 2019). Many researchers such as Appuhami and Bhuyan (2015), Baldini andLiberatore (2016), andHaji (2015) only used some proxies such as audit committees, commissioners, and ownership but they were observed to be clearly weak because the practices of good governance practices cover several aspects.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…The results of most of these studies showed a better corporate governance increases the awareness of companies in expressing intellectual capital and this consequently means the disclosure becomes wider (Abeysekera, 2010;Ahmed Haji & Mubaraq, 2015;Akben-Selcuk & Sener, 2019;Taliyang & Jusop, 2011) but a contrasting finding was reported by Yan (2017). Meanwhile, mixed results were recorded by Appuhami and Bhuyan (2015); Baldini and Liberatore (2016) and this was suggested to be due to the variables used in measuring corporate governance sincere there were no universally agreed measures (Akben-Selcuk & Sener, 2019). Many researchers such as Appuhami and Bhuyan (2015), Baldini andLiberatore (2016), andHaji (2015) only used some proxies such as audit committees, commissioners, and ownership but they were observed to be clearly weak because the practices of good governance practices cover several aspects.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…The explanatory variables were chosen based on two important criterions; one, the standard variables representing board characteristics which were used in similar prior works was chosen for this model. This includes size of the board and its independence(Li et al, 2008;Muttakin et al, 2015;Baldini and Liberatore, 2016). Secondly, availability of data for the selected firms was considered, e.g.…”
mentioning
confidence: 99%
“…Analysis of the components of business administration, study of methods and tools of enterprise management, research of conceptual and empirical approaches to conduct of business administration, and consideration of factors and indicators of quantitative and qualitative evaluation of business administration are studied in the articles of such scholars as (Salvioni and Gennari, 2016), (Al-Maghzom et al, 2016), (Metushi et al, 2016), (Whiting and Birch, 2016), (Baldini and Liberatore, 2016), (Chu et al, 2016), etc. Problems of business administration and marketing management are studied in articles of (Sozinova & Fokina, 2015).…”
Section: Methodsmentioning
confidence: 99%